Differential routing and disposition of the long-chain saturated fatty acid palmitate in rodent vs human beta-cells - Patricia Thomas; Catherine Arden; Jenna Corcoran; Christian Hacker; Hannah J. Welters; Noel G. Morgan (Nutrition & Diabetes, 2022)
Abstract Background Rodent and human β-cells are differentially susceptible to the “lipotoxic” effects of long-chain saturated fatty acids (LC-SFA) but the factors accounting for this are unclear. Here, we have studied the intracellular disposition of the LC-SFA palmitate in human vs rodent β–cells and present data that reveal new insights into the factors regulating β-cell lipotoxicity. Methods The subcellular distribution of the LC-SFA palmitate was studied in rodent (INS-1E and INS-1 823/13 cells) and human (EndoC-βH1) β-cells using confocal fluorescence and electron microscopy (EM). Protein expression was assessed by Western blotting and cell viability, by vital dye staining. Results Exposure of INS-1 cells to palmitate for 24 h led to loss of viability, whereas EndoC-βH1 cells remained viable even after 72 h of treatment with a high concentration (1 mM) of palmitate. Use of the fluorescent palmitate analogue BODIPY FL C16 revealed an early localisation of the LC-SFA to the Golgi apparatus in INS-1 cells and this correlated with distention of intracellular membranes, visualised under the EM. Despite this, the PERK-dependent ER stress pathway was not activated under these conditions. By contrast, BODIPY FL C16 did not accumulate in the Golgi apparatus in EndoC-βH1 cells but, rather, co-localised with the lipid droplet-associated protein, PLIN2, suggesting preferential routing into lipid droplets. When INS-1 cells were treated with a combination of palmitate plus oleate, the toxic effects of palmitate were attenuated and BODIPY FL C16 localised primarily with PLIN2 but not with a Golgi marker. Conclusion In rodent β-cells, palmitate accumulates in the Golgi apparatus at early time points whereas, in EndoC- βH1 cells, it is routed preferentially into lipid droplets. This may account for the differential sensitivity of rodent vs human β-cells to “lipotoxicity” since manoeuvres leading to the incorporation of palmitate into lipid droplets is associated with the maintenance of cell viability in both cell types.